A phase II, multicenter trial of weekly topotecan in patients with recurrent platinum-sensitive epithelial cancers of the ovary and peritoneum. Issue 2 (1st February 2008) - Brown, J. V.; Rettenmaier, M. A.; Lopez, K. L.; Graham, C.; Micha, J. P.; Goldstein, B.
Abstract : The purpose of this study was to evaluate the response rate and toxicity of weekly topotecan in patients with recurrent platinum-sensitive epithelial cancers of the ovary and peritoneum. Thirty-nine platinum-sensitive recurrent ovarian cancer patients received topotecan (4 mg/m 2 ) intravenously day 1, day 8, day 15, every 28 days. Colony-stimulating factors were excluded from the study. Clinical response was assessed by clinical, serologic, and radiographic measures at the conclusion of cycle four. Patients received 136 cycles of topotecan (median = 3; range 1–6) and were evaluated for response and toxicity. Median number of prior regimens was one. Grade 3/4 neutropenia developed in 3 (7.7%) patients. Grade 3 thrombocytopenia was seen in one (2.6%) patient, with no incidence of grade 4 thrombocytopenia. There was no evidence of grade 3 anemia, but one patient (2.6%) was associated with grade 4 anemia. There was no grade 3 or 4 neuropathy. We encountered 18 dose reductions following less than or equal to grade 2 myelosuppression, necessitating the removal of eight (20.5%) patients prior to cycle four. Twenty-one (53.8%) patients were removed from the study due to disease progression. Following the completion of cycle four, four (10.3%) patients demonstrated stable disease and four (10.3%) patients exhibited a partial response. There were no complete responses. Median disease-free survival was 12 weeks. Weekly topotecan (4 mg/m 2 ) demonstrated modest activity and was moderately well tolerated. However, the significant number of dose reductions and high incidence of patients who demonstrated disease progression suggests additional modifications with this specific regimen are necessary.